Using Virtual Reality to Teach Islamic History to Middle School Students - Moh. Sirojud Tolibiin; M. Makhrus Ali (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study investigates the use of Virtual Reality (VR) as an innovative tool to teach Islamic history to middle school students, aiming to enhance engagement, understanding, and retention of historical concepts. VR provides immersive experiences that allow students to explore historical sites, significant events, and cultural artifacts in a realistic and interactive environment. The research employs a qualitative descriptive method with classroom implementation, observation, and interviews as primary data collection techniques. The findings reveal that VR-based learning significantly increases student motivation and curiosity compared to traditional teaching methods. Students demonstrated higher participation, better comprehension of historical timelines, and improved long-term memory retention of key Islamic historical events. However, challenges such as limited access to VR devices, teacher training, and potential technical issues were identified. Overall, integrating VR into Islamic history lessons offers a promising approach to creating engaging, interactive, and meaningful learning experiences for middle school students in the digital age.